2019
DOI: 10.1093/cid/ciz1126
|View full text |Cite
|
Sign up to set email alerts
|

Engagement in Care, Viral Suppression, Drug Resistance, and Reasons for Nonengagement After Home-Based Same-Day Antiretroviral Therapy Initiation in Lesotho: A Two-Year Follow-up of the CASCADE Trial

Abstract: Background The CASCADE trial showed that compared with usual care (UC), offering same-day (SD) antiretroviral therapy (ART) during home-based human immunodeficiency virus testing improved engagement in care and viral suppression 12 months after diagnosis. However, questions remain regarding long-term outcomes and the risk of propagating drug resistance. Methods After completion of the primary endpoint at 12 months, participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 26 publications
1
24
0
Order By: Relevance
“…When compared to standard of care (facility-based ART initiation and refills), retention did not appear to differ by population type, ART initiation site, refill site, or frequency of ART refill ( Fig 5 ). One study additionally reported retention among HIV-positive individuals at 24 months and found no difference between community ART initiation and facility ART initiation and maintenance (RD 5%, 95% CI −16% to 16%, p = 0.380) at this time point [ 33 ]. In pooled analyses restricted to those who initiated ART, retention was no different between study arms ( S6 Fig ; RR 1.15, 95% CI 0.99 to 1.33).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…When compared to standard of care (facility-based ART initiation and refills), retention did not appear to differ by population type, ART initiation site, refill site, or frequency of ART refill ( Fig 5 ). One study additionally reported retention among HIV-positive individuals at 24 months and found no difference between community ART initiation and facility ART initiation and maintenance (RD 5%, 95% CI −16% to 16%, p = 0.380) at this time point [ 33 ]. In pooled analyses restricted to those who initiated ART, retention was no different between study arms ( S6 Fig ; RR 1.15, 95% CI 0.99 to 1.33).…”
Section: Resultsmentioning
confidence: 99%
“…Three studies compared viral suppression between community ART initiation and facility ART initiation and maintenance (standard of care) arms among HIV-positive individuals at 12 months; this comparison showed better viral suppression in the community ART group (RR 1.31, 95% CI 1.15 to 1.49) ( Fig 6 ). One study additionally reported 24-month outcomes, which showed no difference in viral load suppression in the community ART arm compared to the facility ART arm (RD 3%, 95% CI −9% to 15%, p = 0.28) at this time point [ 33 ]. The threshold for viral load suppression ranged from less than 100 copies/mL [ 23 ], to 1,000 copies/mL [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…24 If clients are transferred to ART refills outside the clinic (eg, decentralised dispensing, adherence groups, community, and home) compared with clinic ART, they remained virally supressed. [25][26][27] Offering convenient locations and times after hours and on weekends, being flexible to meet travel or mobility needs, offering quarterly refills, and streamlining monitoring and resupply had better viral suppression outcomes, especially for men.…”
Section: Discussionmentioning
confidence: 99%